2020
DOI: 10.1002/iub.2338
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA ZEB2‐AS1: A promising biomarker in human cancers

Abstract: Long non‐coding RNAs (lncRNAs) are one of the ncRNAs that transcript with length more than 200 nt that are not translated into protein. Studies have shown that lncRNAs have regulatory function in human disease especially cancers. lncRNA dysfunction causes altered cellular behavior including proliferation, invasion, and migration, and also it can inhibit apoptosis. Long non‐coding zinc finger E‐box binding homeobox 2 antisense RNA1 (lnZEB2‐AS1) is one of the lncRNAs that plays the oncogenic role in different ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Some DEirlncRNAs in the 40 IRLP signature have been validated to be involved in the occurrence and development of tumors. lncZEB2-AS1 and MEF2C-AS1 have been demonstrated as poor biomarkers for patients with BRCA [ 24 , 25 ]. Our data indicated those IRLPs are in particular related to MAPK signaling, Jak-STAT signaling, and ErbB signaling pathways in BRCA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some DEirlncRNAs in the 40 IRLP signature have been validated to be involved in the occurrence and development of tumors. lncZEB2-AS1 and MEF2C-AS1 have been demonstrated as poor biomarkers for patients with BRCA [ 24 , 25 ]. Our data indicated those IRLPs are in particular related to MAPK signaling, Jak-STAT signaling, and ErbB signaling pathways in BRCA.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired ERBB2 expression or function has been implicated in the progression of breast and gastric cancers [ 26 ], mainly through targeting the PI3K/AKT and MAPK pathways [ 27 ]. Previous studies also demonstrated that some DEirlcnRNAs can modulate those pathways such as lncRNA-ZEB2-AS1 and MEF2C-AS1 [ 24 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…and its high expression level has been implicated in many cancers (Guo et al, 2018;Mahboobeh et al, 2020;F. Wu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Theragnostics is the nexus point of therapeutics and diagnostics and describes a system to customize healthcare using molecular and genetic tools for treatment decisions tailored to an individual patient [ 159 ]. The emerging functions of many lncRNAs as oncogenes in several carcinomas promoting different steps in carcinogenesis, such as escape to control cellular systems, cell proliferation and migration, aberrant and enhanced metabolism, impaired and deregulated epigenetic landscape, and metastasis, have pointed out lncRNAs as potential therapeutic targets in the breaking of tumorigenesis [ 160 , 161 ]. The importance of lncRNAs in each and every one of these processes has led to the design of different strategies and molecules that allow repressing the function or expression of the lncRNAs, since in most of the examples described, blocking the lncRNA function would be translated in repression of the aggressiveness of cancer accompanied by the reduction of several promoting processes related to carcinogenesis [ 162 ].…”
Section: Development Of Strategies To Obtain the Blocking Oncogene Fu...mentioning
confidence: 99%